Ovarian Teratomas in Children and Adolescents: Our Own Experience and Review of Literature - Fani Gkrozou; Orestis Tsonis; Anastasia Vatopoulou; Georgia Galaziou; Minas Paschopoulos (MDPI AG, 2022)
Background: Ovarian teratomas are the most common type of ovarian mass during childhood and adolescence. There is no clear guidance for the management of the ovarian teratomas in children and adolescents. It is necessary, however, to understand the feature of these tumours and the indications for operating on them, and to put subjective criteria for the management in elective or emergency presentations. Methods: Medical records of patients between the age of 12 and 20 years old that underwent surgery for ovarian teratomas at the Department of Obstetrics and Gynaecology in University Hospital of Ioannina, between January 2000 and August 2022, were reviewed. A medical database was searched between January 2000 and August 2022 with the following keywords: ovarian teratoma, paediatrics and adolescents. Results: We present the results of forty patients, with a mean age of 11.8 years of age. All patients had surgery, where three out of four underwent oophorectomy and only one out of four underwent ovary-sparing operation; similar results were found in the literature. Conclusion: Ovary-sparing treatment is more common recently compared with the past, such as MIS compared with laparotomy. Better-organised and -planned prospective multi-centre studies are necessary to gain a deeper knowledge of the physiology and prognostic factors of teratomas in children.